2019
DOI: 10.1177/0300060519866279
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for burnout among postgraduate chemistry education students

Abstract: Objective This study investigated the efficacy of a group rational emotive behavioural intervention for burnout among postgraduate chemistry education students in Nigeria. Method Participants were 36 postgraduate chemistry education students with high burnout symptoms; 18 students were randomly assigned to an experimental group and 18 to a control group. The Oldenburg Burnout Inventory – Student Version was used to assess burnout. Results There was no significant difference between the experimental group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…This finding is in line with a study which explored gender differences in burnout of students in Nigeria (Arumede et al, 2019). Furthermore, a previous study showed among 36 postgraduate students, a no significant difference in pretest mean burnout scores (Ezeudu, et al, 2019). But on the long run, experimental group posttest scores showed a significant enhancement compared with both experimental group pretest scores and with control group posttest scores (Ezeudu, et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding is in line with a study which explored gender differences in burnout of students in Nigeria (Arumede et al, 2019). Furthermore, a previous study showed among 36 postgraduate students, a no significant difference in pretest mean burnout scores (Ezeudu, et al, 2019). But on the long run, experimental group posttest scores showed a significant enhancement compared with both experimental group pretest scores and with control group posttest scores (Ezeudu, et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a previous study showed among 36 postgraduate students, a no significant difference in pretest mean burnout scores (Ezeudu, et al, 2019). But on the long run, experimental group posttest scores showed a significant enhancement compared with both experimental group pretest scores and with control group posttest scores (Ezeudu, et al, 2019). Another recent study treating academic burnout of undergraduates found that the pre-test results indicated no significant difference in the burnout scores of the students (Ezeudu, et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The result further sustains recent evidence that REBT intervention programs are effective and can decrease student learning burnout. [3942] This finding suggests the need to deal with the burnout of electrical and building construction undergraduate before full occupation entry. Otherwise, these set of vocational and technical students will enter into their occupation with symptoms of burnout syndrome.…”
Section: Discussionmentioning
confidence: 99%